Ethnobotanical Study of Aren (Arenga pinnata) Plant by Banjar Tribe in Banyu Irang Village, Bati-bati Sub-district, Tanah Laut Regency - Norfajrina, Norfajrina (Universitas Tanjungpura, 2025)
Ar palm plants have benefits for the Banjar people, but their utilisation is not widely known in local wisdom-based ethnobotanical studies. This study aims to describe 6 aspects of ethnobotanical studies of sugar palm plants in Banyu Irang Village, Bati-bati District, Tanah Laut Regency, South Kalimantan. This research is a field research using snowball sampling method with data collection techniques of observation, semi-structured interview, and documentation. The results of botanical studies show that this plant is a palm tree with fibrous roots and erect trunks. Ethnopharmacologically, aren palm plants are used for traditional medicine, especially to aid digestion and detoxification. In ethnosocio-anthropological studies, aren palm plants are used in various traditional ceremonies and mystical beliefs, such as its fibre rope that is believed to ward off misfortune. In ethnoeconomic studies, aren palm plants can be made into various processed foods, such as brown sugar (gula habang), a drink called banyu lahang, and kolang-kaling. In ethnolinguistic studies, local people call this plant by the term Hanau, which has been passed down from generation to generation. Ethnoecological studies show that palm trees thrive in riverbank and swamp environments. This research is expected to contribute to the conservation of palm trees while maintaining the local wisdom of the people of Banyu Irang Village.